Effect of Carbodiimide Crosslinking on Gelatin-Carboxymethylcellulose-Polycaprolactone Scaffold Properties for Wound Dressing Applications - Sriswat, Manus; Wiwatwongwana, Fasai (Engineering, Technology & Applied Science Research, 2025)
This research investigated the feasibility of fabricating 3D porous scaffolds from gelatin, carboxymethylcellulose (CMC) and polycaprolactone (PCL) using the freeze-drying technique for wound dressing applications. The scaffolds were crosslinked using Dehydrothermal Treatment (DHT) and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) combination with N-hydroxysuccinimide (NHS). Their morphological and mechanical properties were analyzed to determine the optimal condition. For DHT crosslinking, the results demonstrated that the average pore size ranged from 127.25 to 150.77 µm, which was smaller than in non-crosslinked scaffolds. The porosity ranged from 64.84% to72.08%, decreasing as CMC content increased. The gelatin scaffold with 35% (w/w) CMC and 30% (w/w) PCL exhibited the best overall properties. It provided the highest average pore size and porosity, and a compressive strength of 47.39 MPa, which was higher than non-crosslinked scaffold. Under EDC/NHS conditions, the average pore size ranged from 145.40 µm to 184.80 µm and porosity from 70.24% to 74.48%. These characteristics indicate a larger pore size and porosity compared to the DHT crosslinked scaffold Although its compressive strength was lower than that of the DHT crosslinked scaffold, it remained higher than that of the non-crosslinked scaffold. Therefore, it can be implied that the gelatin scaffold with 35% CMC and 30% PCL is suitable for use as a skin substitute in wound dressing applications